Peace Theology in the Hudaibiyah Agreement: Actualization of the Values of the Faith from the Perspective of Qashash Al-Qur'an - Nuraini, Nuraini; Yani, Sri Rahma; Aslati, Aslati; Agustin, Hanna Jenifer; S, Mochammad Novendri (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2026)
This study examines the theology of peace embodied in the Treaty of Hudaybiyyah through the perspective of Qashash al-Qur'an (Qur'anic narratives), with a particular focus on the actualization of creedal values (aqidah) relevant to the lives of Muslims. The Treaty of Hudaybiyyah represents one of the most monumental events in Islamic history, not only reflecting the diplomatic strategy of Prophet Muhammad (peace be upon him) but also demonstrating theological principles grounded in faith, patience, obedience, and commitment to peace. From the Qur'anic perspective, this event is portrayed as a victory containing profound wisdom for strengthening faith and shaping the moral character of the Muslim community. This research aims to identify the creedal values embedded in the narrative of the Treaty of Hudaybiyyah based on the interpretations of Qur'anic exegetes, while also analyzing their relevance in constructing a theology of peace amid the dynamics of contemporary Muslim society. This study employs a library research method using a thematic interpretation (mawdhu'i) approach within the framework of Qashash al-Qur'an studies. Primary data were obtained from various Qur'anic commentaries discussing the verses related to the Treaty of Hudaybiyyah, particularly those contained in Surah al-Fath. Secondary data were drawn from Islamic historical literature, scholarly articles, and other relevant academic studies. All data were analyzed using content analysis techniques to uncover the meanings, values, and theological messages embedded in this event. The findings reveal that the Treaty of Hudaybiyyah embodies several creedal values that serve as the foundation of the theology of peace in Islam. These include belief in Allah's wisdom behind every divine decree, patience in facing trials and pressures, obedience to the decisions of the Prophet Muhammad (peace be upon him), commitment to agreements and covenants, and the spirit of consultation (shura) in resolving conflicts. These values possess strong relevance in modern life, particularly in fostering a culture of tolerance, strengthening moderate attitudes, promoting peaceful conflict resolution, and cultivating optimism and trust in the wisdom underlying every circumstance faced by Muslims. Penelitian ini mengkaji teologi perdamaian yang terkandung dalam Perjanjian Hudaibiyah melalui perspektif qashash al-Qur’an dengan menitikberatkan pada aktualisasi nilai-nilai akidah yang relevan bagi kehidupan umat Islam. Perjanjian Hudaibiyah merupakan salah satu peristiwa monumental dalam sejarah Islam yang tidak hanya merepresentasikan strategi diplomasi Nabi Muhammad saw., tetapi juga mencerminkan prinsip-prinsip teologis yang berlandaskan keimanan, kesabaran, ketaatan, dan komitmen terhadap perdamaian. Dalam perspektif al-Qur’an, peristiwa ini diposisikan sebagai kemenangan yang mengandung hikmah besar bagi penguatan akidah dan pembentukan karakter umat. Penelitian ini bertujuan untuk mengidentifikasi nilai-nilai akidah yang terkandung dalam kisah Perjanjian Hudaibiyah berdasarkan penafsiran para mufasir, sekaligus menganalisis relevansinya dalam membangun teologi perdamaian di tengah dinamika kehidupan masyarakat Muslim kontemporer. Penelitian ini merupakan penelitian kepustakaan (library research) dengan menggunakan pendekatan tafsir tematik (maudhu‘i) dalam kerangka kajian qashash al-Qur’an. Data primer diperoleh dari berbagai kitab tafsir yang membahas ayat-ayat terkait Perjanjian Hudaibiyah, khususnya yang termuat dalam Surah al-Fath, sedangkan data sekunder bersumber dari literatur sejarah Islam, artikel ilmiah, dan kajian akademik yang relevan. Seluruh data dianalisis menggunakan teknik content analysis untuk mengungkap makna, nilai, dan pesan teologis yang terkandung dalam peristiwa tersebut. Hasil penelitian menunjukkan bahwa Perjanjian Hudaibiyah mengandung sejumlah nilai akidah yang menjadi fondasi teologi perdamaian dalam Islam, yaitu keyakinan terhadap kebijaksanaan Allah dalam setiap ketetapan-Nya, kesabaran dalam menghadapi ujian dan tekanan, kepatuhan terhadap keputusan Rasulullah saw., komitmen terhadap perjanjian, serta semangat musyawarah dalam menyelesaikan konflik. Nilai-nilai tersebut memiliki relevansi yang kuat dalam konteks kehidupan modern, terutama dalam membangun budaya toleransi, memperkuat sikap moderat, mengedepankan penyelesaian konflik secara damai, serta menumbuhkan optimisme dan kepercayaan terhadap hikmah di balik setiap peristiwa yang dihadapi umat Islam.